Recursos hídricos superficiais da área urbana e de expansão da cidade de São Carlos, SP - estudo multitemporal - Molina Junior, Vitor Eduardo (2003)
The purpose of achieving a multitemporal study of evolution of impacts in the hydric resources for São Carlos city, SP, it was elaborated an analysis of interaction among the superficial hydric resources and fountainhead of the studied area with the urban evolution from 1962 to 2002. Besides, it was observed how the execution of forestal code was given in the studied periods . To reach the research´s purposes, the sceneries were obtained from 1962, 1972, 1998 and 2002 using the techniques of remote sensoring and GIS. For the sceneries of 1962 and 1972, aerial photos were used in the approximate scale of 1:25000. For the scenery of 1998, aerial photos were used in the scale of 1:8000, and for the scenery of 2002, orbital image Landsat 7 Etm+ was used. From the obtained results, it was possible to detect that the hydric resources suffered interference of urban evolution, like bury of fountainhead and impermeabilization of the canal of streams and areas around these ones. At last, the work showed a description of impacts of superficials hydrics resources and some areas were emphasized that must be protected to guarantee the sustainable of hydrics resources that weren´t affected by antrophic action, yet.